Can Children Enhance Their Family's Health Knowledge? An Infectious Disease Prevention Program - Sedighi, Iraj (Tehran University of Medical Sciences, 2012)
OBJECTIVE: The purpose of this study is to propose an innovative method of knowledge transfer that aims to improve health literacy about pediatric infectious diseases prevention in families. Children have an appreciable role in this scheme. METHODS: This study is a before and after trial that has been conducted in Hamedan in 2009. After changing seven infectious disease topics into childish poems, we selected five kindergartens randomly and taught these poetries to the children. Teaching process held after a pretest containing 24 questions that examined 103 of parents about mentioned topics. The same post-test was given after 4 months of teaching process. FINDINGS: The mean of correct answers to the pretest was 59.22% comparable with 81.00% for post-test (P<0.00). Gender and knowledge degree could not change the results significantly. Assuming one's correct answers to the questions as his/her Knowledge Mark, the mean of this variable increased to 5.32 by this method. CONCLUSION: This cost-effective and joyful method had successful results in promoting health knowledge. Children are able to play an active role in family's health situation. Learning within family atmosphere without any obligations makes our scheme a solution for paving the knowledge transferring way.